2017
DOI: 10.1253/circj.cj-17-0128
|View full text |Cite
|
Sign up to set email alerts
|

Ranolazine Facilitates Termination of Ventricular Tachyarrhythmia Associated With Acute Myocardial Ischemia Through Suppression of Late <b><i>I</i></b><sub>Na</sub>-Mediated Focal Activity

Abstract: of Na + channel inactivation, may contribute to arrhythmogenesis in a variety of pathological conditions. 7-10 Late INa is small in normal cardiac myocytes and is enhanced by heart failure, exposure to oxidative stress, hypoxia and ischemia/reperfusion. 7-10 Late INa during the action potential (AP) plateau reduces repolarization reserve and may prolong AP duration (APD), which renders the membrane potential vulnerable for early afterdepolarization (EAD). In addition, increased late INa-dependent sarcolemmal N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Previously Ogawa et al showed that acute ranolazine perfusion facilitated the termination of ischemic VT/ VF by the suppression of I Na,L -dependent focal arrhythmogenic activity in isolated rabbit hearts 12 . Dhalla et al reported that ranolazine markedly reduced IR-induced VAs possibly via its I Na,L inhibitor property to reduce afterdepolarizations 11 .…”
Section: Discussionmentioning
confidence: 98%
“…Previously Ogawa et al showed that acute ranolazine perfusion facilitated the termination of ischemic VT/ VF by the suppression of I Na,L -dependent focal arrhythmogenic activity in isolated rabbit hearts 12 . Dhalla et al reported that ranolazine markedly reduced IR-induced VAs possibly via its I Na,L inhibitor property to reduce afterdepolarizations 11 .…”
Section: Discussionmentioning
confidence: 98%
“…Ranolazine's antiarrhythmic action during AMI has been shown to be mediated by inhibition of increased I NaL rather than by I Kr blockade. [5][6][7]9 This can be explained by a reduction in I NaL which in turn may decrease Na-dependent Ca 2þ overload, suggesting as a potential mechanism of EADs. However, since the arrhythmogenic substrate during the late post-MI period is different and the mechanism of VAs is more likely linked to reentry, I NaL blockade cannot effectively assist in preventing such arrhythmias solely on the basis of an EAD-suppressing mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Increased late sodium current (I NaL ) in the ischemically damaged myocardium may account as a mechanism for ectopic activity, generating after-potentials during repolarization due to sodium-overload mediated increased cytosolic calcium. 4 Although blockade of this current with ranolazine, a acetanilide and piperazine derivative that inhibits the I NaL at therapeutic doses, has been suggested to be responsible for a substantial antiarrhythmic effect against ventricular arrhythmias (VAs) observed during AMI, [5][6][7] its impact for VAs occurring several days postmyocardial infarction has not yet been explored.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to above experimental observations about the alteration in ionic currents upon exposure to CO, it should be noted that CO can also indirectly contribute to the cellular electrophysiological remodeling via myocardial ischemia. Under the ischemic condition, intracellular acidosis activates the Na + /H + exchanger to exclude hydrogen ions in exchange for sodium ions, and the elevated sodium is then exchanged for calcium through the Na + /Ca 2+ exchanger, which finally leads to intracellular Ca 2+ overload (115,116). Acidosis also inhibits I CaL , and this effect results in APD shortening together with the reduced I KATP by hypoxia (115).…”
Section: Potential Proarrhythmic Mechanismsmentioning
confidence: 99%